SUSTAINING CLASS INTERACTION AND COLLABORATIVE LEARNING IN A VIRTUAL CLASSROOM - Karlina Karadila Yustisia; Malikhatul Lailiyah; Cinta Lia Fitriana (Journal of English Educational Study (JEES), 2023)
The teaching and learning activity must continue even in any situation or time, and most educational settings use online learning to keep it on the path. To achieve specific goals in 21st-century learning skills, improving students' collaborative skills in problem-solving, solution-finding, decision-making, and bargaining is crucial. The main focus of the investigation was how to improve students' collaborative learning when learning a language. This research explained the phase applied to progress the class interaction through collaborative learning in a virtual classroom. In the learning process, the students were divided into two groups. The first was the learning group, where the students gained knowledge, then regrouped in the teaching group and presented what they had learned from the learning group. Six open-ended questions were given to assess the students’ knowledge-building and experience in the learning and teaching groups. Research showed that most students agreed and were satisfied with this group collaboration activity in a virtual classroom. The result also indicated that students perceive group work satisfaction positively, with an average mean of 3.7. By utilizing video-teleconference technologies to their full potential, students can engage in virtual networking interactions and develop close relationships to solve problems with one another. Even if the entire teaching and learning process takes place online, the students can still engage in discussions with each small group which could result in collaborative learning.